Sistem Bisnis Waralaba Restoran Ayam Bakar Wong Solo dalam Perspektif Ekonomi Islam - Rahman, Taufiqur (MarÃ¢ji`: Jurnal Ilmu Keislaman, 2015)
This article tries to analyze the franchise business system of Ayam Bakar Wong Solo Restaurant through the Islamic economics perspective. The franchise business system applied by the Ayam Bakar Wong Solo is a cooperation (shirkah) with the type of shirkah mudârabah, where there is a cooperation between the Ayam Bakar Wong Solo as a manager (mudârib) and investors as owners of capital (sahib al-mâl). Both parties allied in the venture capital and the advantage of the alliance is divided in accordance with the agreements that have been agreed between the two. The Ayam Bakar Wong Solo offers two forms of shirkah mudârabah, namely mudârabah mutlaqah and mudârabah muqayyadah. It is found that there is a correspondence between the execution of the Ayam Bakar Wong Solo franchise and shirkah mudârabah practices in Islamic economics because the franchise system which is run has been suitably qualified and has met the rukn of shirkah mudârabah. However, there is a concept of franchis-ing which is more in line with Islamic economics, namely the principle of sharing in mudârabah and mushârakah as a substitute for a franchise concept with franchise fee and royalty fee.